Effect of Force Frequency Increase on Depth of Cut - Tewari S.P.; Rathod N. (My University, 2025)
In this paper, the study is perform to check the dynamic behavior of metal cutting by using two expressions, given by two different researchers. Kronenberg performed various experiments and established a relation to find the frequency of vibration during metal cutting. Afterwards Singh performed his work on elastic deformation during metal cutting and analytically derived an expression for determining frequency of vibration during metal cutting. In the present study, turning operation is performed on mild steel at various cutting speeds, feeds and depth of cuts. Chips are collected and analyzed and hence frequency of vibration during cutting is calculated by the expressions given by Kronenberg and Singh. Experimental results and analytical results were compared and both were having good correlation. © 2012, The Institution of Engineers (India).